A well-preserved aneuretopsychid from the Jehol Biota of China (Insecta, Mecoptera, Aneuretopsychidae) - Ren, Dong (Pensoft Publishers, 2011)
Abstract. The Aneuretopsychidae is an unspeciose and enigmatic family of long-proboscid insects that presently consist of one known genus and three species from the Late Jurassic to Early Cretaceous of north-central Asia. In this paper, a new genus and species of fossil aneuretopsychid is described and illustrated, Jeholopsyche liaoningensis gen. et sp. n. Fossils representing this new taxon were collected from mid Early Cretaceous strata of the well known Jehol Biota in Liaoning Province, China. This finding documents the first formal record of fossil Aneuretopsychidae in China. In addition, this well-preserved and new material reveals previously unknown and detailed morphological structure of the mouthparts, antennae, head, thorax, legs and abdomen of this distinctive insect lineage.